The efficacy and safety of chidamide in combination with etoposide and glucocorticoids for the treatment of hemophagocytic lymphohistiocytosis in adult patients: an open-label, single-center study - Hu, Junxia; Wang, Jingshi; Wang, Zhao (Frontiers in Immunology, 2024)
Background Hemophagocytic lymphohistiocytosis (HLH) is a life-threatening condition characterized by hyperinflammation and organ failure, with a high mortality rate. Current first-line treatments for adult patients have limited efficacy and significant toxicity. The novel selective histone deacetylase inhibitor (HDACi), chidamide, has shown promise in preclinical studies for the potential treatment of HLH. Methods An open-label, single-center study was conducted to evaluate the efficacy and safety of chidamide in combination with etoposide and glucocorticoids for the treatment of HLH in adult patients. Seventeen patients who fulfilled at least five of the eight HLH-2004 criteria were enrolled and treated with the combination therapy. The primary outcome was overall response rate (ORR), and secondary outcomes included survival, safety and tolerability, and changes in laboratory indicators. Results A total of 17 HLH patients who met the inclusion criteria were enrolled in this study, with a male to female ratio of 1.8:1. The age range at enrollment was 31 to 71 years old, with a median age of 52 years old. The ORR was 76.5% (13/17 patients), with a complete response (CR) rate of 17.6% (3/17 patients) and a partial response (PR) rate of 58.8% (10/17 patients). The median overall survival (OS) was not achieved, with OS at 6 months and 12 months being 81% and 65%, respectively. The median progression free survival (PFS) was not achieved, with PFS at 6 months and 12 months being 68% and 55%, respectively. Hematologic toxicities is the most common. Safety profile was favorable, with very few cases of grade 3/4 toxicities observed. The results showed that the levels of sCD25, platelets, aspartate aminotransferase, lactate dehydrogenase, and albumin in these patients were significantly improved 3 weeks after treatment. Conclusion The addition of chidamide to etoposide and glucocorticoids may be a promising new treatment option for patients with HLH, with a high ORR, manageable safety profile, and significant improvement in laboratory indicators. Further research is needed to confirm these findings and determine the optimal dosing and duration of therapy.